Modulation of social behavior by distinct vasopressin sources - Rigney, Nicole; de Vries, Geert J.; Petrulis, Aras (Frontiers in Endocrinology, 2023)
The neuropeptide arginine-vasopressin (AVP) is well known for its peripheral effects on blood pressure and antidiuresis. However, AVP also modulates various social and anxiety-related behaviors by its actions in the brain, often sex-specifically, with effects typically being stronger in males than in females. AVP in the nervous system originates from several distinct sources which are, in turn, regulated by different inputs and regulatory factors. Based on both direct and indirect evidence, we can begin to define the specific roles of AVP cell populations in social behavior, such as, social recognition, affiliation, pair bonding, parental behavior, mate competition, aggression, and social stress. Sex differences in function may be apparent in both sexually-dimorphic structures as well as ones without prominent structural differences within the hypothalamus. The understanding of how AVP systems are organized and function may ultimately lead to better therapeutic interventions for psychiatric disorders characterized by social deficits.